The Impact of São Paulo faz Escola Program on newly Qualified Teachers - Ricardo Abdalla Barros; Maria Antonia Ramos de Azevedo (Universidade Federal do Rio Grande do Sul, 2016)
This study aimed to enhance reflections about the teaching of Portuguese language and literature newly qualified teachers who work with São Paulo Faz Escola Program. We conducted a qualitative research through a case study by means of analysis of documents, interviews and follow-up of these teachers. The data showed the feeling that the authorship and the autonomy of professional intervention were taken of these teachers. Besides, we observed the pressure suffered by teachers so that students have good grades in merely quantitative assessments, completely disregarding all they lived along the school year.